2007
DOI: 10.1111/j.1365-2605.2007.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of a 38‐kDa capacitation‐associated buffalo (Bubalus bubalis) sperm protein is induced by L‐arginine and regulated through a cAMP/PKA‐independent pathway

Abstract: The aim of the present study was to determine the effect of L-arginine on nitric oxide (NO*) synthesis, capacitation and protein tyrosine phosphorylation in buffalo spermatozoa. Ejaculated buffalo spermatozoa were capacitated in the absence or presence of heparin, or L-arginine or N(omega)-nitro-L-arginine methyl ester (L-NAME), an inhibitor of nitric oxide synthase (NOS) for 6 h. Capacitating spermatozoa generated NO* both spontaneously and following stimulation with L-arginine and L-NAME quenched such L-argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
3
18
0
1
Order By: Relevance
“…2). Such a dose-dependent increase of broadly distributed protein tyrosine phosphorylation during sperm capacitation has also been reported in cattle and buffalo, by using other capacitation inducers [20, 21, 24, 25]. It has been accepted that cAMP elevation and subsequent PKA activation is necessary for protein tyrosine phosphorylation in sperm [26].…”
Section: Discussionmentioning
confidence: 75%
“…2). Such a dose-dependent increase of broadly distributed protein tyrosine phosphorylation during sperm capacitation has also been reported in cattle and buffalo, by using other capacitation inducers [20, 21, 24, 25]. It has been accepted that cAMP elevation and subsequent PKA activation is necessary for protein tyrosine phosphorylation in sperm [26].…”
Section: Discussionmentioning
confidence: 75%
“…The situation of phosphorylated proteins at the principal piece of the flagellum has been related to motility hyperactivation and to the presence of A-kinase anchoring proteins (which anchor PKA) located in the fibrous sheath of the sperm flagellum in several species (Carrera et al 1996, Mandal et al 1999, Jha & Shivaji 2002a, Pommer et al 2003. Conversely, a capacitation-related redistribution of phosphotyrosine residues to the acrosome has been reported in humans (Naz et al 1991), boars (Tardif et al 2001, Dube et al 2005, bulls (Cormier & Bailey 2003) and buffalo (Roy & Atreja 2008). Moreover, other studies have revealed that certain tyrosine phosphoproteins become localized to the sperm surface overlying the acrosome during capacitation suggesting a key role of these proteins in sperm-zona binding (Asquith et al 2004, Piehler et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a capacitation-associated redistribution of phosphotyrosine residues to the acrosome has been reported in boars (Petrunkina et al 2001, Tardif et al 2001, bulls (Cormier & Bailey 2003) and buffalo (Roy & Atreja 2008), and specific phosphotyrosine proteins localized over the acrosomal region have been postulated to be involved in the zona pellucida interaction and/or fusion events (Leyton & Saling 1989, Naz et al 1991, Ficarro et al 2003, Dube et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Although both serine/threonine phosphorylation and tyrosine phosphorylation of proteins have been reported in spermatozoa, the tyrosine phosphorylation of a number of protein substrates has been associated with capacitation in the spermatozoa of most mammalian species, and is considered a hallmark event of capacitation. [16][17][18][19][20][21] Several tyrosine phosphoproteins in capacitated buffalo and cattle spermatozoa were identified using 2D immunoblotting and mass spectrometry. These include serine/threonine-protein phosphatase PP1c2 catalytic subunit, the MGC157332 protein, alpha-enolase, 3-oxoacid CoA transferase 2 and actin-like protein 7A.…”
Section: Protein Tyrosine Phosphorylationmentioning
confidence: 99%